2020
DOI: 10.3390/ijerph17186620
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Infection Risks among Clients and Staff Who Use Tattooing Services in Poland: An Observational Study

Abstract: Across cultures and generations, people have tattooed their bodies. Although blood-borne infections from tattooing have been reduced, certain service aspects remain improperly managed. We assessed the infection risks associated with tattooing by conducting a cross-sectional study (2013–2014) in Poland using an anonymous questionnaire survey. Scoring procedures for blood-borne infection risks for tattooists and their clients were used. Overall, 255 tattooists were interviewed. A quasi-random selection of tattoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…According to the recent study assessing infection risk among clients and staff of Polish tattoo services, only one-third of the questioned tattooists indicated that they had attended training concerning infection prophylaxis, postexposure, sterilization, and disinfection procedures. Moreover, 1 in 5 of those tattoo artists reported having needlestick injuries while tattooing their customers [20]. Without proper knowledge concerning the transmission of infectious diseases and precautions that could be taken to limit the risks, tattooing remains a threat for both clients and tattooists.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…According to the recent study assessing infection risk among clients and staff of Polish tattoo services, only one-third of the questioned tattooists indicated that they had attended training concerning infection prophylaxis, postexposure, sterilization, and disinfection procedures. Moreover, 1 in 5 of those tattoo artists reported having needlestick injuries while tattooing their customers [20]. Without proper knowledge concerning the transmission of infectious diseases and precautions that could be taken to limit the risks, tattooing remains a threat for both clients and tattooists.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Furthermore, in the last years, a dangerous unregulated market of tattoo removal by cosmetologists, tattooists, nurses, and nonspecialized physicians has emerged, together with "do-it-yourself" tattoo removal procedures [12]. Some authors emphasized that the health risks in this service sector concern both clients and even professionals and therefore risk knowledge is fundamental to guarantee bilateral safety [12,13].…”
Section: Introductionmentioning
confidence: 99%